Spirits and Letters Reading, Writing and Charisma in African Christianity. - Kirsch, Thomas G. (New York : Berghahn Books, Inc., 2008)
Studies of religion have a tendency to conceptualise 'the Spirit' and 'the Letter' as mutually exclusive and intrinsically antagonistic. However, the history of religions abounds in cases where charismatic leaders deliberately refer to and make use of writings. This book challenges prevailing scholarly notions of the relationship between 'charisma' and 'institution' by analysing reading and writing practices in contemporary Christianity. Taking up the continuing anthropological interest in Pentecostal-charismatic Christianity, and representing the first book-length treatment of literacy practi.
CH 11-Missions in writingCH 12-Enablements to literacy; Part IV-Bureaucracy in the Pentecostal-Charismatic mode; CH 13-Offices and the Dispersion of Charisma; CH 14-Positions of writers, positions in writings; CH 15-Outlines for the future, documents of the immediate; CH 16-Bureaucracy in-between; CH 17-Epilogue; Bibliography; Index.
Description based on print version record.
Keywords: Religion; Christianity -- Africa; RELIGION / Christianity / History; Electronic books